Comparison of clinical parameters, microbiological effects and calprotectin counts in gingival crevicular fluid between Er: YAG laser and conventional periodontal therapies. Issue 51 (December 2017) - Wang, Yue; Li, Weiwei; Shi, Li; Zhang, Fengqiu; Zheng, Sun
Abstract: Background: The erbium-doped yttrium, aluminum, and garnet (Er:YAG) laser is thought to be the most promising laser for periodontal treatment; however, its application is still under consideration. The aim of this study was to compare Er:YAG laser monotherapy with conventional scaling and root planing (SRP) for chronic periodontitis using clinical parameters, the detection rate of periodontal pathogens, and the calprotectin level in gingival crevicular fluid. Methods: Twenty-seven participants with moderate-to-advanced chronic periodontitis were included. In a split-mouth design, the 2 half-mouths of each participant were randomly assigned to Er:YAG laser or SRP (combination of ultrasonic and manual instruments) treatment. Clinical parameters were recorded at baseline, 6 weeks, and 3 and 6 months after treatment. At the same time points, gingival crevicular fluid was collected to analyze the detection rate of 6 periodontal pathogens by polymerase chain reaction and the levels of calprotectin by enzyme-linked immunosorbent assay. Results: Both treatment groups showed significant reductions in probing depth (PD), bleeding index (BI), and clinical attachment level (CAL) from baseline to 6 months. For sites with 4 mm ⩽ PD ⩽ 6 mm at baseline, SRP resulted in a greater reduction in PD and CAL than Er:YAG laser treatment, and the difference remained at 6 months post-treatment ( P  = .01 and P  < .01, respectively). For sites with PD ≥7 mm at baseline, the clinical parameters showed similar results between the 2 groups. SRP resulted in a lower detection rate of Porphyromonas gingivalis at 6 months post-treatment. The levels of calprotectin were significantly decreased from baseline to 6 months in both groups, without a significant difference between the groups. Conclusion: For mild pockets, conventional SRP may still be the preferred choice. For deep pockets, Er:YAG laser treatment could be an effective alternative. Studies are needed to explore more advanced instruments and new application methods for the Er:YAG laser for periodontal treatment in deep pockets. Abstract : Supplemental Digital Content is available in the text